Coarse‐grained models for studying protein diffusion along DNA. (27th April 2016) - Bhattacherjee, Arnab; Krepel, Dana; Levy, Yaakov
Abstract : Understanding the molecular mechanism and the fast kinetics of DNA target site recognition by a protein is essential to decipher genetic activity in the cell. The speed of searching DNA may depend on the structural complexity of the proteins and the DNA molecules as well as the cellular environment. Coarse‐grained (CG) molecular dynamics simulations are powerful means to investigate the molecular details of the search performed by protein to locate the target sites. Recent studies showed how different proteins scan DNA and how the search efficiency can be enhanced and regulated by the protein properties. In this review, we discuss computational approaches to study the physical chemistry of DNA search processes using CG molecular dynamics simulations and their advantage in covering long time‐scale biomolecular processes. WIREs Comput Mol Sci 2016, 6:515–531. doi: 10.1002/wcms.1262 This article is categorized under: Structure and Mechanism > Computational Biochemistry and Biophysics Abstract :